Post mortem diagnosis of Fasciola hepatica in cattle slaughtered at the Sogamoso, Boyacá processing plant (Boyacá, Colombia) - Ortiz-Pineda, Melissa Camila (2021)
The aim of this study was to determine the prevalence of hepatic dystomatosis in cattle slaughtered in the Sogamoso slaughterhouse (Boyacá, Colombia), and to define the most effective diagnostic technique to establish the presence of the parasite. A sample size of 343 individuals was established considering the monthly slaughter rate of the plant. Stool, blood and bile samples were taken, and adult parasites were collected from the bile duct. The modified Ritchie technique was used in the coproparasitological examination, the bile content was analyzed by sedimentation and a standardized in-house ELISA was implemented for serological diagnosis from adult Fasciola hepatica parasites. The results showed that 29.7% (102/343) of the individuals sampled were positive for the presence of F. hepatica in at least one of the techniques used. The post mortem evaluation presented the highest value (19.8%; 68/343), followed by the in-house ELISA (13.7%; 47/343), detection of eggs in bile (117%; 40/343) and the coprological technique (7.3%; 25/343).